Diesel and welding aerosols in an underground mine - Bugarski, Aleksandar D.; Barone, Teresa L.; Hummer, Jon A. (International journal of mining science and technology, 2020)
Researchers from the National Institute for Occupational Safety and Health (NIOSH) conducted a study in an isolated zone of an underground mine to characterize aerosols generated by: (1) a diesel-powered personnel carrier vehicle operated over a simulated light-duty cycle and (2) the simulated repair of existing equipment using manual metal arc welding (MMAW). Both the diesel-powered vehicle and MMAW process contributed to concentrations of nano and ultrafine aerosols in the mine air. The welding process also contributed to aerosols with electrical mobility and aerodynamic mobility count median diameters of approximately 140 and 480 nm, respectively. The welding particles collected on the filters contained carbon, iron, manganese, calcium, and aluminum.